Targeted Drug Delivery to the Spleen and Its Implications for the Prevention and Treatment of Cancer - Ikramy A. Khalil; Ahmed Faheem; Mohamed El-Tanani (Pharmaceutics)
The spleen, the largest secondary lymphoid organ, plays several vital roles in the body, including blood filtration, hematopoiesis, and immune regulation. Despite its importance, the spleen has not received substantial attention as a target organ for drug delivery. Most systemically administered colloidal and particulate drug carriers are cleared from the blood by the liver and spleen, making these two organs potential targets for drug accumulation. While various systems have been developed to target the liver, there is an urgent need to design spleen-targeted drug delivery systems that can evade clearance and degradation while delivering drugs efficiently to their target cells in the spleen. Targeting the spleen holds great potential for the treatment of a range of diseases, including blood disorders, immune and inflammatory diseases, infectious diseases, and cancer. It is also crucial for the development of effective vaccines. In this review, we explore different approaches used to target the spleen after systemic administration, and we discuss the factors that shift the biodistribution of drug carriers from the liver to the spleen. We focus on cell-specific delivery within the spleen, strategies to avoid degradation, and methods to achieve the efficient intracellular delivery of various drugs and genes. We also highlight the therapeutic implications of spleen-targeted drug delivery systems, particularly for the prevention and treatment of cancer.